The Effect of Digital Literacy, Soft Skills, and Learning Motivation on Student Learning Achievement - Aznikhah, Uli; Fitriyani, Suci; Hartono, Edy (International Journal of Business, Economics, and Social Development, 2025)
This study aims to analyze the effect of digital literacy, soft skills, and learning motivation on students' academic achievement at private universities in Cirebon. The approach used in this study is a quantitative method. The research locations include several private universities in Cirebon. The research population was all students of the Faculty of Economics in the 2024-2025 academic year. The sample used was 100 students, selected through a stratified random sampling technique proportionally to obtain a balanced representation. Determination of the sample size was carried out using the Slovin formula. Data were collected by distributing a 1-5 Likert scale questionnaire using Google Form. Data analysis was carried out using IBM SPSS Statistic 26.0 software through classical assumption tests such as normality and multicollinearity tests, multiple linear regression tests, and coefficient of determination tests. The results of the multiple linear regression analysis on the t-test showed that digital literacy had a positive and significant effect on learning achievement with evidence of 3.185 > 1.984; soft skills have a positive and significant effect with a value of 4.145 > 1.984; and learning motivation does not have a positive and significant effect on learning achievement as evidenced by a value of 1.266 < 1.984. Based on these results, it can be concluded that digital literacy and soft skills have a positive and significant effect on student learning achievement at private universities in Cirebon. While learning motivation does not have a positive and significant effect on student learning achievement at private universities in Cirebon.